THE EFFECT OF ONE HOUSE ONE LARVAE OBSERVER MOVEMENT ON THE EXISTENCE OF MOSQUITO LARVAE IN WATUBANGGA SUBDISTRICT: HOUSE AND LARVAE OBSERVER - Yanti Susanti; Timbul Supodo; Sunarsih Sunarsih (STIKes Mandala Waluya Kendari, 2022)
Background: Dengue Hemorrhagic Fever is a mosquito-borne infectious disease found in tropical and subtropical areas around the world. In recent years, transmission has increased especially in urban and semi-urban areas and has become a major international public health concern. The aim of this study was to analyze the effect of the movement of one house and one larva monitor on the presence of larvae in Watubangga sub-district, Watubangga sub-district. Methods: This type of research is quantitative research with a pre-experimental approach. The population in this study were all heads of families living in the Watubangga Village area as many as 608 families. The sample in the study was partly from the heads of families who lived in Watubangga Village as many as 236 respondents. The sample was selected using a systematic random sampling method. Data were collected through questionnaires and observation sheets and then analyzed descriptively and inferentially. Result: This study shows that there is an effect of the movement of one house and one larva monitoring interpreter on the presence of larvae in Watubangga Village where a p-value of 0.000 is obtained. Conclusion: After the intervention with the one house movement, one larva monitoring interpreter, there was an increase in community skills in efforts to prevent dengue hemorrhagic fever. Therefore, it is hoped that the one house one larva monitoring program can be implemented throughout the territory of the Republic of Indonesia.